2022
DOI: 10.1155/2022/4186305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Data-CT Radiomics-Based Model for Predicting Prognosis of Patients with Gastrointestinal Pancreatic Neuroendocrine Neoplasms (GP-NENs)

Abstract: Purpose. Based on computerized tomography (CT) radiomics and clinical data, a model was established to predict the prognosis of patients with gastrointestinal pancreatic neuroendocrine neoplasms (GP-NENs). Methods. In the data collection, the clinical imaging and survival follow-up data of 225 GP-NENs patients admitted to Xiangyang No.1 People’s Hospital and Jiangsu Province Hospital of Chinese Medicine from August 2015 to February 2021 were collected. According to the follow-up results, they were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In terms of disease recurrence appraisal, clinical data may significantly impact when added to radiomic features, as shown by one study [ 121 ] on 225 GP-NETs. Considering radiomics scores and clinical pathological factors (age, Ki-67 index, tumor pathological type, tumor primary site, and TNM stage), An et al [ 121 ] were able to properly assess the non-recurrent group and the recurrent group more accurately than the individual models, which analyzed independently (combined model with an AUC of 0.824; clinical data model with an AUC of 0.786, and radiomics model with an AUC of 0.712).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of disease recurrence appraisal, clinical data may significantly impact when added to radiomic features, as shown by one study [ 121 ] on 225 GP-NETs. Considering radiomics scores and clinical pathological factors (age, Ki-67 index, tumor pathological type, tumor primary site, and TNM stage), An et al [ 121 ] were able to properly assess the non-recurrent group and the recurrent group more accurately than the individual models, which analyzed independently (combined model with an AUC of 0.824; clinical data model with an AUC of 0.786, and radiomics model with an AUC of 0.712).…”
Section: Resultsmentioning
confidence: 99%
“…First-order statistics were also the best predictors for distinguishing PNETs from PDACs [ 63 , 64 ]. Ultimately, the best performance was achieved when radiomics features were combined with clinical features [ 69 , 110 , 111 , 121 ]. All this evidence still needs to be reproduced in a larger cohort of patients and in a prospective manner to ensure reliability.…”
Section: Prospects and Limitsmentioning
confidence: 99%
“…In recent years, radiomics has been gradually and widely used in the diagnosis of cancers (10), identification of molecular typing of tumors (11), prediction of survival status of patients (12), and the use of imaging genomics to analyze the relationship between imaging features and genomic features to dissect tumor heterogeneity (13). Radiomics studies targeting NETs are also increasing, and radiomics can be applied in the diagnosis of pancreatic NETs (14), predicting the grading of pancreatic NETs (15), determining the prognosis of NETs (16), and assessing the effects of drug therapy for NETs (17). However, there are few radiomics studies for NECs, Wang et al (18) identified gastric NECs from gastric adenocarcinoma with CT radiomics.…”
Section: Introductionmentioning
confidence: 99%